Fundamental accounting principles - Larson, Kermit D.; Wild, John J.; Chiappetta, Barbara (Boston : McGraw-Hill/Irwin, 2002)
Business
2002-06-05
Keywords: Accounting; Accounting information; Managerial accounting; Cost accounting